2024
DOI: 10.1002/ejlt.202300115
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of spent coffee ground as a natural antioxidant and its use for sunflower oil shelf‐life extension

Laila Bijla,
Asma Hmitti,
Angela Fadda
et al.

Abstract: In the present paper, spent coffee grounds (SCG) were investigated for their antioxidant capacity, chemical profiling, and their potential to extend the shelf‐life of refined sunflower oil (RSO). Ethanolic SCG extract (SCGE) ability to enhance RSO oxidation, during accelerated aging conditions, was examined at 60°C for 120 days. To this end, oxidative stability was evaluated for RSO added with SCGE (at 0.01%, 0.02%, and 0.03%) in the presence of a negative control (RSO without SCGE) and a positive one consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Previous studies recorded similar observations regarding the resistance of edible oils to thermal degradation. [19,40,41] Previous studies recorded similar results. [19,40] For instance, Chandrasekar et al [40] showed that incorporated rutin esters delayed the progress of the oxidation of sardine oil compared to the untreated or enriched sardine oil.…”
Section: Conjugated Dienes During Accelerated Oxidationsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies recorded similar observations regarding the resistance of edible oils to thermal degradation. [19,40,41] Previous studies recorded similar results. [19,40] For instance, Chandrasekar et al [40] showed that incorporated rutin esters delayed the progress of the oxidation of sardine oil compared to the untreated or enriched sardine oil.…”
Section: Conjugated Dienes During Accelerated Oxidationsupporting
confidence: 64%
“…Vegetable oils commonly contain adequate levels of pigments, for example, chlorophylls, pheophytins, and carotenoids, which are related to their characteristic color and also contribute to their stability against rancidity due to their known antioxidant activity. [19,41] The relative content of pigments during the thermo-induced oxidation was assessed by fluorescence spectroscopy. Figures S5 and S6 depict the relative decrease in pigments' content, which is associated with the emission peak at 670 nm.…”
Section: Pigment Contentmentioning
confidence: 99%
“…The determination of the oil pigment content followed the protocol outlined by [24]. In a 25 mL volumetric flask, approximately 7.5 g of each oil sample was placed and then diluted with cyclohexane to reach a volume of 25 mL.…”
Section: Determination Of Pigment Contentmentioning
confidence: 99%
“…The chlorophyll and pheophytin profile may experience further modifications, with pheophytinization leading to a decrease in chlorophyll levels [86]. Bijla et al claimed that enrichment with 0.01, 0.02, and 0.03% vitamin E led to a reduction in chlorophyll levels by approximately 45% over four months of accelerated storage [24]. Carotenoids, meanwhile, are tetra-terpenoids that can give orange, red, and yellow hues, playing a vital role in the coloration of oils.…”
Section: Effect Of Thermal Storage On Pigment Contentmentioning
confidence: 99%
See 1 more Smart Citation